"Sustainability" a semi-globalisable concept for international food marketing: Consumer expectations regarding sustainable food - An explorative survey in industrialised and emerging countries - Marie von Meyer-Höfer; Achim Spiller (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Today's global food production and consumption often stand in sharp contrast to the objectives of sustainable development. Sustainable food products, characterised by higher environmental or ethical standards than conventional equivalents, are therefore an essential mean of addressing this global challenge. However, to ensure uptake of these products it is crucial for agri-food market actors to understand consumer expectations regarding sustainable food, so they can appropriately tailor their differentiation and communication strategies. To explore these consumer expectations, data from an online survey in three industrialised and three emerging countries is used. The results show that consumers around the globe have quite diverse expectations regarding sustainable food products. Only very few attributes such as 'environmental friendly production', 'no chemical pesticides', 'naturalness' and 'safety' can be used to meet a range of international consumers' expectations regarding sustainable food. International food marketers should thus try to get to know their consumers in each country better and learn how to address them specifically, i.e., by semi-global marketing strategies.
Keywords: Q13; Q18; 330; sustainable food consumption; consumer expectations; international marketing; semiglobalisation